Gender Inequalities in Rural European Communities During 19th and Early 20th Century A Historical Perspective - Thanailaki, Polly (Springer International Publishing, 2018)
This book provides an overview of women's opportunities for schooling, their social activities, and the social biases they faced in rural communities in Greece, Italy and parts of the Balkans during the 19th and early 20th century. It examines such topics as female illiteracy, the efforts of women-protestant missionaries to expand knowledge through Protestantism, the prejudice against education for women, the socio-economic context, the roles women fulfilled, and the structure of the patriarchal family. The book approaches these issues from the perspective of pedagogy and social history. The fundamental questions discussed by the book are: How was female education viewed by the country folk? What was the role of women in the private and the public sphere? How did peasant women respond to the challenges of the 'modern' world? Were they free to express their feelings and ambitions? In what way? Were they happy?